PERAN KEPALA DESA DALAM MENYELESAIKAN KONFLIK ANTAR WARGA DI DESA MAMUYA KECAMATAN GALELA KABUPATEN HALMAHERA UTARA - Sugi, Sofyan (HOLISTIK, Journal Of Social and Culture, 2014)
Every day in the life of a human being in a community of mutual need for each other. In the community are expected to be created by the harmony of life in between; family life, religion, and society and prevent yourself from conflict. Conflict is an act that we don't want shared, because a result inflicted can hurt many people and very dangerous. Post conflict fought in North Halmahera Regency around the year 1999-2000 which many take its toll making the community of North Halmahera did not want this to happen again The village of Mamuya horizontal conflicts around January of 2014, conflict occurs as a result of some citizens of Mamuya wanted to separate himself from the communion of Evangelical Christian Church in Halmahera (GMIH) into a Special Synod Council (SSI). This makes the community GMIH Church in particular started Mamuya disturbed by the presence of another Fellowship at the village of Mamuya. And this conflict arose because there were some of them has been a provocateur and creating unrest that citizens, especially the GMIH Christian Mamuya also as a community that is in the village of Mamuya with residents who broke away from an alliance with each other GMIH hitting, and even kill each other's citizens want. Therefore local communities desperately need attention and handling of the authorities of the village. But, until recently seen the lack of attention from the Government as a facilitator in the village of resolving conflicts between citizens, resulting in the community from both sides was his life is no longer in harmony as original headquarters was created.. Keywords : conflict, church, facilitator